Pulmonary Tuberculosis Screening in Diabetes Mellitus Patients at Klinik Cahaya Kemang - Pujiastuti (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2025)
The relationship between Tuberculosis (TB) and Diabetes Mellitus (DM) is intricate and intertwined, posing significant global health challenges. In addition, the increasing prevalence of DM worldwide raises concerns regarding the potential resurgence of tuberculosis. The implementation of tuberculosis prevention strategies is of the most importance, especially in countries like Indonesia that encounter a dual burden of TB and DM. The significance of TB screening in private primary care settings for patients with diabetes cannot be overstated. Implementing TB screening protocols in private primary care settings can assist in identifying diabetic patients with tuberculosis. This study aims to evaluate the implementation and outcomes of pulmonary TB screening in DM patients at Cahaya Kemang Clinic throughout 2024. A retrospective descriptive study was conducted using secondary data from the Prolanis DM program and TB screening records at Cahaya Kemang Clinic from January to December 2024. A total of 7 DM patients were screened, and 1 (14.8%) case of pulmonary TB was confirmed by GeneXpert testing. Routine TB screening in DM patients is essential and effective in early detection and treatment of TB.